Evaluating Hammermill Tip Speed, Air Assist, and Screen Hole Diameter on Ground Corn Characteristics - Michaela B. Braun; Kara M. Dunmire; Haley K. Wecker; Chad B. Paulk; Charles R. Stark; Michael W. Sodak; Maks Kapetanovich; Jerry Shepherd; Randy Fisher; Kyle Coble (Kansas Agricultural Experiment Station Research Reports, 2021)
Whole yellow dent #2 corn was ground using two 43 mm Andritz hammermills (Model: 4330-6, Andritz Feed & Biofuel, Muncy, PA; JBS Live Pork LLC Feed Mill, Fremont, IA). Both mills discharged to a shared plenum where samples were collected via a sample port. Each mill was equipped with 72 hammers and 300 HP motors on a variable frequency drive (VFD). Corn was ground on 3 separate days to create replication and treatments were randomized within replication. Treatments were arranged in a 3 × 3 × 3 factorial design with 3 tip speeds (12,383, 16,323, and 20,263 ft/min); 3 screen hole diameters (6/64, 10/64, and 16/64 in.); and 3 air assist system fan RPM’s (60, 80, and 100% of fan motor load). Samples of each treatment were collected and analyzed for moisture, particle size, and flowability characteristics. Particle size analysis was completed using a 13-sieve stack with the inclusion of sieve agitators and flow agent. Flowability characteristics were evaluated using a composite flow index (CFI), which includes percent compressibility, angle of repose (AoR), and critical orifice diameter (COD). Data were analyzed as a 3 × 3 × 3 factorial using the PROC GLIMMIX procedure of SAS with grinding run as the experimental unit and sample collection day as a blocking factor. There were no 3-way interactions for screen hole diameter × hammer tip speed × air flow for the geometric mean diameter (dgw) or any flowability characteristics of ground corn. There was a 3-way interaction for particle size standard deviation (Sgw), (linear screen hole diameter × linear hammer tip speed × linear air flow,P= 0.029). There was a linear screen hole diameter × linear hammer tip speed interaction (P = 0.001) for dgw. When tip speed increased from 12,383 to 20,263 ft/min, the rate of decrease in dgwwas greater as screen hole diameter increased from 6/64 to 16/64 in. An interaction of screen hole diameter and hammer tip speed (linear × linear,P= 0.040) was also observed for the CFI. The CFI results increased with increasing screen hole diameter when corn was ground using a hammer tip speed of 12,383 ft/min but no differences were observed as tip speed increased to 16,323 and 20,263 ft/min. An interaction of screen hole diameter and hammer tip speed (quadratic × quadratic,P= 0.001) was observed for mill motor load. Mill motor load decreased as screen hole diameter increased from 6/64 in. to 16/64 in., but increased as hammer tip speed was increased with the most significant reductions being observed as tip speed increased from 12,383 ft/min to 16,323 ft/min on the 6/64 in. screen. In conclusion, hammer tip speed and air flow rate are viable options for adjusting ground material characteristics when grinding using a hammermill, alongside the traditional screen variations. Along with the range of particle sizes capable of being produced, an increased level of accuracy can also be achieved with hammer tip speed and air flow adjustments with minimal down time necessary for screen changes.
Keywords: hammermill; hammer tip speed; air assist; screen hole diameter; particle size